Tumor genomic, transcriptomic, and immune profiling characterizes differential response to first‐line platinum chemotherapy in high grade serous ovarian cancer. (3rd April 2021) - Weberpals, Johanne I.; Pugh, Trevor J.; Marco‐Casanova, Paola; Goss, Glenwood D.; Andrews Wright, Natalie; Rath, Prisni; Torchia, Jonathon; Fortuna, Alexander; Jones, Gemma N.; Roudier, Martine P.; Bernard, Laurence; Lo, Bryan; et al.
Abstract: Background: In high grade serous ovarian cancer (HGSOC), there is a spectrum of sensitivity to first line platinum‐based chemotherapy. This study molecularly characterizes HGSOC patients from two distinct groups of chemotherapy responders (good vs. poor). Methods: Following primary debulking surgery and intravenous carboplatin/paclitaxel, women with stage III–IV HGSOC were grouped by response. Patients in the good response (GR) and poor response (PR) groups respectively had a progression‐free intervals (PFI) of ≥12 and ≤6 months. Analysis of surgical specimens interrogated genomic and immunologic features using whole exome sequencing. RNA‐sequencing detected gene expression outliers and inference of immune infiltrate, with validation by targeted NanoString arrays. PD‐L1 expression was scored by immunohistochemistry (IHC). Results: A total of 39 patient samples were analyzed (GR = 20; PR = 19). Median PFI for GR and PR patient cohorts was 32 and 3 months, respectively. GR tumors were enriched for loss‐of‐function BRCA2 mutations and had a significantly higher nonsynonymous mutation rate compared to PR tumors ( p  = 0.001). Samples from the PR cohort were characterized by mutations in MGA and RAD51B and trended towards a greater rate of amplification of PIK3CA, MECOM, and ATR in comparison to GR tumors. Gene expression analysis by NanoString correlated increased PARP4 with PR and increased PD ‐ L1 and EMSY with GR. There was greater tumor immune cell infiltration and higher immune cell PD‐L1 protein expression in the GR group. Conclusions: Our research demonstrates that tumors from HGSOC patients responding poorly to first line chemotherapy have a distinct molecular profile characterized by actionable drug targets including PARP4. Abstract : In patients with suboptimally‐debulked, advanced high grade serous ovarian cancer (HGSOC), the spectrum of responses to first line platinum‐based chemotherapy (PtC) vary from durable to non‐existent, highlighting an unmet medical need for those with poor responses. Our study molecularly characterizes a cohort of HGSOC patients with distinct responses, either good or poor, to PtC. The good and poor responders have median progression‐free intervals of 32 and 3 months, respectively, and molecular analysis of tumors identifies differences in DNA damage response pathways and immunity, namely, tumors from poor responders to first line PtC have a distinct molecular profile characterized by actionable drug targets including PARP4.